2020
DOI: 10.1080/21655979.2020.1831362
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidics for the rapid detection of Staphylococcus aureus using antibody-coated microspheres

Abstract: Staphylococcus aureus is a common foodborne pathogenic microorganism which can cause food poisoning and it is pathogenic to both humans and animals. Therefore, rapid detection of S. aureus infection is of great significance. In this study, a microfluidic platform was introduced to detect S. aureus by fluorescence labeling method and a self-made microfluidic chip, which has immune spheres were used to study the effect of capturing S. aureus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The Ng strain was reconstituted from frozen stock cultures and propagated at 37°C with 5% CO 2 on GC agar (OXOID, Basingstoke, UK). Before each treatment, the bacterial concentration was adjusted to 5 × 10 6 CFU mL −1 (colony-forming units per milliliter)[ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…The Ng strain was reconstituted from frozen stock cultures and propagated at 37°C with 5% CO 2 on GC agar (OXOID, Basingstoke, UK). Before each treatment, the bacterial concentration was adjusted to 5 × 10 6 CFU mL −1 (colony-forming units per milliliter)[ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…For 2 μL/min flow rate, the fluorescence intensity reaches its maximum functionality, while a 5 μL/min flow rate and a 4 min duration are the optimal conditions for the optimal injection and reaction. At this flow rate, the target bacteria can be seen from the microsphere’s surface [ 209 ].…”
Section: Microfluidics and Locs In Food Safety Applicationsmentioning
confidence: 99%
“…in the sample measured by the microchip was approximately 12 CFU/ml. Song et al (2020) developed a microfluidic platform to detect S. aureus by fluorescence labeling method and a self-made microfluidic chip, which has immune spheres were used to study the effect of capturing S. aureus ( Figure 4C ). Results showed that our platform can detect S. aureus at an injection rate of 5 μl/min reacted for 4 min and the detection limit of bacteria was 1.5 × 10 1 CFU/mul.…”
Section: Microfluidic Detection Technologymentioning
confidence: 99%
“… (A) Schematic of this Colorimetric Biosensor for Detection of Salmonella ( Xue et al, 2021 ); (B) Making the process of the microchip ( Zhang et al, 2021b ); (C) The whole process of a microfluidic platform for detection of S. aureus by fluorescence labeling ( Song et al, 2020 ); (D) Schematics of the i-Gene ( Nguyen et al, 2020 ). …”
Section: Microfluidic Detection Technologymentioning
confidence: 99%